Coeliac disease – a review of concepts and new developments - Pedro, Nelson (2009)
Coeliac disease is a chronic enteropathy that remains a challenge to the clinician and the investigator, due to its atypical manifestations and aetiopathogenic complexity. Recent research in this area, enables the detection of silent forms of the disease and has made possible an assessment of its real prevalence, which is higher than initially thought.This article reviews clinical, epidemiological and physiopathological concepts in coeliac disease, bringing up to date concepts revealed by the latest research (especially in the genetic domain) and medical publications; we suggest a schematic approach to the disease based on these recent developments.We proceeded to research articles from archives of Medline/Pubmed/Medscape, and from specific sites from the World Wide Web of medical magazines, published in the last years, particularly review articles and investigational data concerning coeliac disease. We also proceeded, to research the National Portuguese journals, textbooks and scientific meetings about coeliac disease.